If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28=6(x+3)-4x
We move all terms to the left:
28-(6(x+3)-4x)=0
We calculate terms in parentheses: -(6(x+3)-4x), so:We get rid of parentheses
6(x+3)-4x
We add all the numbers together, and all the variables
-4x+6(x+3)
We multiply parentheses
-4x+6x+18
We add all the numbers together, and all the variables
2x+18
Back to the equation:
-(2x+18)
-2x-18+28=0
We add all the numbers together, and all the variables
-2x+10=0
We move all terms containing x to the left, all other terms to the right
-2x=-10
x=-10/-2
x=+5
| 6b+7=325 | | 0.06y=1.8 | | X/2+17=5x/8+4-x | | 2x+17=5x/8+4-x | | 7x+2-3x=14 | | X/2+5x/8=21-x | | 2x/5+3x/5=8+3 | | 8x-5-2x=25 | | 3n+9=5n-7 | | 7+4x(4-1)=19 | | 2x-4+9x=40 | | ─9r+4r─11+2=3r+7─8r+9 | | 32(40-4.5x)=16(4x-7)+60.8 | | 3(m-2)-2=4(m-4) | | 7(x-2)=-3(x+3)+33 | | 7(x—49)—5(x+49)=63–5(x—49) | | (2x)(5x)(11x)=360 | | q^2-q=42 | | 9t+81=0 | | |10+2x|+8=10 | | -x/2=59 | | -41=y/6 | | (5y+8)(8+y)=0 | | 8x=11.2 | | -20=2x(x-9) | | 2+3y=4y-4 | | -4(2y-8)+4y=6(y+6) | | 14=8x/29 | | -9u+14=-5(u-2) | | 4x-26+5x+3+7x+7=180 | | 4(x-6)-6x=-4 | | 2(5x-18)=180 |